Responsible Innovation and the Innovation of Responsibility: Governing Sustainable Development in a Globalized World - Voegtlin, Christian (Journal of business ethics, 2017)
Earth’s life-support system is facing megaproblems of sustainability. One important way of how these problems can be addressed is through innovation. This paper argues that responsible innovation that contributes to sustainable development (SD) consists of three dimensions: (1) innovations avoid harming people and the planet, (2) innovations ‘do good’ by offering new products, services, or technologies that foster SD, and (3) global governance schemes are in place that facilitate innovations that avoid harm and ‘do good.’ The paper discusses global governance schemes based on deliberation as a means to foster such responsible innovation. These schemes can provide voluntary soft-law regulations that complement and extend national and international hard-law regulations and facilitate collective innovation that contributes to SD goals. The article addresses the facilitative role of governments and international organizations in overcoming problems of deliberation and offers illustrative examples of such governance schemes.